Direct immunofluorescence in bullous disorders: A mini-review - Pant, Anil Dev (Journal of Pathology of Nepal, 2024)
Background: Immunofluorescence microscopy is an invaluable tool for different lesions in dermatopathology. These lesions include bullous lesions, vasculitis, and connective tissue disorders/systemic lupus erythematosus. In this review, we take a look at bullous disorders. Some of these diagnoses are not possible on routine histopathology alone and require immunofluorescence for confirmation. Different diseases can be diagnosed according to the immunoglobulins/complements, sites of deposition (dermo-epidermal / intercellular spaces / dermal), and their patterns (linear, granular). Knowing the exact type of lesion can help guide treatment accordingly.